Intelligent Techniques in Signal Processing for Multimedia Security - Dey, Nilanjan; Santhi, V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book proposes new algorithms to ensure secured communications and prevent unauthorized data exchange in secured multimedia systems. Focusing on numerous applications' algorithms and scenarios, it offers an in-depth analysis of data hiding technologies including watermarking, cryptography, encryption, copy control, and authentication. The authors present a framework for visual data hiding technologies that resolves emerging problems of modern multimedia applications in several contexts including the medical, healthcare, education, and wireless communication networking domains. Further, it introduces several intelligent security techniques with real-time implementation. As part of its comprehensive coverage, the book discusses contemporary multimedia authentication and fingerprinting techniques, while also proposing personal authentication/recognition systems based on hand images, surveillance system security using gait recognition, face recognition under restricted constraints such as dry/wet face conditions, and three-dimensional face identification using the approach developed here. This book equips perception technology professionals with the latest technologies, techniques, and strategies for multimedia security systems, offering a valuable resource for engineers and researchers working to develop security systems.
Security of Multimedia Contents: A Brief -- A Survey on Intelligent Security Techniques for High Definition Multimedia Data -- Intelligent Morphing and Steganography Techniques for Multimedia Security -- Information Hiding: Steganography -- Digital Watermarking: A Potential Solution For Multimedia Authentication -- Real Time Implementation of Reversible Watermarking -- Comparative Approach between Singular Value Decomposition and Randomized Singular Value Decomposition based watermarking -- Biometric Based Security System: Issues and Challenges -- Parametric Evaluation of Different Cryptographic Techniques for Enhancement of Energy Efficiency in Wireless Communication Network -- Hand Image based Personal Authentication System -- A Study on Security and Surveillance System using Gait Recognition -- Face Recognition under Dry and Wet Face Conditions -- Improved Approach for 3D Face Characterization -- Attendance Recording System using Partial Face Recognition Algorithm -- Automatic Human Emotion Recognition in Surveillance Video -- Watermarking in Bio-medical Signal Processing -- Pixel Repetition Technique: A high capacity and reversible data hiding method for e-healthcare applications -- A New method of Haar and Db10 based Secured Compressed Data Transmission over GSM Voice Channel -- StegNmark: A Joint Stego-Watermark Approach for Early Tamper Detection -- Adaptive Color Image Watermarking Scheme Using Weibull Distribution -- Multi-Fingerprint Unimodel based Biometric Authentication Supporting Cloud Computing.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Multimedia systems; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Multimedia Information Systems